Effects of Momordica cochinchinensis Aril Extract on Sterilized Low-Fat Milk, Antioxidant and Antiproliferative Activities - Thitiporn Anunthawan; Santi Phosri; Jirayus Woraratphoka; Rasapirose Somwatcharajit; Panee Terdsaksri; Prangruethai Prangphet (International Journal of Food Science)
The aril extract (0.4% g/mL) of Gac fruit in milk supplement can inhibit cancer cell lines. Moreover, the extract has no toxicity against normal cells. In a sensory test, sterilized low-fat milk supplemented with 0.4% extract did not have different sensory score compared to the control. During the sterilization process, extract was not significantly different from the control. In sterilization (121°C, 15 min), adding Gac fruit extract in low-fat milk results in antioxidant activity increase. The extract increased values for the redness and yellowness of sterilized low fat, but the lightness decreased. Also, the extract slightly decreased the alcohol stability of sterilized low-fat milk. At an accelerated rate (50°C, 28 days), there was no effect of the extract addition on protein aggregation in low-fat milk. Moreover, the TBA values indicate the ability of the extract to inhibit lipid oxidation. Finally, Gac fruit extract added to milk may possibly extend the shelf life of sterilized low-fat milk and improve its antioxidant and anticancer activity properties.